Primary vulvar squamous cell carcinomas with high T cell infiltration and active immune signaling are potential candidates for neoadjuvant PD-1/PD-L1 immunotherapy - Kortekaas, Kim E.; Santegoets, Saskia J.; Tas, Liselotte; Ehsan, Ilina; Charoentong, Pornpimol; Doorn, Helena C. van; Poelgeest, Mariette I. E. van; Mustafa, Dana A. M.; Burg, Sjoerd H. van der (Journal for ImmunoTherapy of Cancer, 2021)
Background A profound insight into the immune landscape of vulvar squamous cell carcinoma (VSCC) is lacking. Here, an in-depth interrogation of T cell infiltration, local immune contexture, signaling pathways and checkpoint molecule expression was performed in early-stage and late-stage VSCC. - Methods The type, location, and infiltration pattern of T cells were studied in 109 patients with primary VSCC FIGO stage I-III. RNA expression of genes involved in immune oncology and oncogenic signaling pathways was analyzed in 40 VSCC, matched for prognostic clinicopathological variables, analyzed for HPV and p53 status, and selected based on T cell infiltration. - Results High intraepithelial infiltration with CD4 or CD8 T cells was associated with longer overall and recurrence-free survival and formed an independent prognostic factor, outperforming molecular subtype and stage of the disease. Strong T cell infiltrated VSCC displayed a coordinated immune response reflected by a positive association between T cells and different lymphocyte and myeloid cell subsets. The expression of genes involved in the migration of T cells and myeloid cells, T cell activation and costimulation, interferon (IFN)-γ signaling, cytotoxicity and apoptosis was higher than in low infiltrated tumors. An active immune signaling profile was observed in all inflamed, part of the altered-excluded and not in altered-immunosuppressed or deserted VSCC. While several checkpoint molecules were overexpressed, only PD-L1 expression displayed discriminatory ability and clinical usefulness. High PD-L1 expression was detected in all inflamed and ~60% of the altered-excluded VSCC. - Conclusion An active immune signaling profile is present in 35% of primary FIGO I-III VSCCs, suggesting potential responsiveness to neoadjuvant PD-1/PD-L1 immunotherapy.
Gesehen am 28.01.2022